Vitamin E hydroquinone is an endogenous regulator of ferroptosis via redox control of 15-lipoxygenase. - Andrew Hinman; Charles R Holst; Joey C Latham; Joel J Bruegger; Gözde Ulas; Kevin P McCusker; Akiko Amagata; Dana Davis; Kevin G Hoff; Amanda H Kahn-Kirby; Virna Kim; Yuko Kosaka; et al. (PLoS ONE, 2018)
Ferroptosis is a form of programmed cell death associated with inflammation, neurodegeneration, and ischemia. Vitamin E (alpha-tocopherol) has been reported to prevent ferroptosis, but the mechanism by which this occurs is controversial. To elucidate the biochemical mechanism of vitamin E activity, we systematically investigated the effects of its major vitamers and metabolites on lipid oxidation and ferroptosis in a striatal cell model. We found that a specific endogenous metabolite of vitamin E, alpha-tocopherol hydroquinone, was a dramatically more potent inhibitor of ferroptosis than its parent compound, and inhibits 15-lipoxygenase via reduction of the enzyme's non-heme iron from its active Fe3+ state to an inactive Fe2+ state. Furthermore, a non-metabolizable isosteric analog of vitamin E which retains antioxidant activity neither inhibited 15-lipoxygenase nor prevented ferroptosis. These results call into question the prevailing model that vitamin E acts predominantly as a non-specific lipophilic antioxidant. We propose that, similar to the other lipophilic vitamins A, D and K, vitamin E is instead a pro-vitamin, with its quinone/hydroquinone metabolites responsible for its anti-ferroptotic cytoprotective activity.